A "Catastrophic" Heparin-Induced Thrombocytopenia. (13th April 2020) - Barcellona, D.; Melis, M.; Floris, G.; Mameli, A.; Muroni, A.; Defazio, G.; Marongiu, F.
Abstract : Background . Heparin-induced thrombocytopenia (HIT) is a transient, antibody-mediated thrombocytopenia syndrome that usually follows exposure to unfractioned heparin (UFH) or low-molecular-weight heparin (LMWH). In contrast to other pathological conditions which lead to thrombocytopenia and bleeding complications, HIT results in a paradoxical prothrombotic state. It is caused by antibodies directed to complexes containing UFH or LMWH and a self-platelet protein: the platelet factor 4 (PF4). The heparin-PF4 immune complex leads to activation of platelets, monocytes, and endothelial cells which release procoagulant proteins and tissue factor with subsequent blood coagulation activation. Case Report . We describe the case of a woman undergone to knee replacement and affected by urosepsis who developed a HIT after exposure to enoxaparin. The thrombotic burden was very impressive involving the arterial and venous cerebral vessel and the venous pulmonary, hepatic, and inferior legs vascular beds. The patient was successfully treated with fondaparinux without recurrent thrombosis or bleeding. The clinical scenario could be named "catastrophic HIT" like the catastrophic antiphospholipid syndrome since they have a similar pathogenetic mechanism involving both platelets and monocytes procoagulant activities and a similar clinical manifestation with a life-threatening multiple arterial and/or venous thromboses. Conclusion . Patients presenting with HIT could show a very impressive thrombotic burden resembling to that of the catastrophic antiphospholipid syndrome. A careful differential diagnosis should be made towards other pathological conditions which lead to thrombocytopenia to avoid an unnecessary and potentially harmful platelet transfusion. Although fondaparinux is off-label, its use in patients with HIT is simple and seems to be effective.